A functional interpretation of continuous variable quantum discord - Assad, S; Chrzanowski, H; Symul, T; Lam, P; Ralph, T; Gu, M; Vedral, V (2011)
We show that quantum discord can quantify the information advantage of a quantum processing over an optimal classical processing. We experimentally extract a lower bound on the quantum discord of a non-entangled continuous-variable quantum system. © 2011 IEEE.